Strategi Kelompok Difabel DIY dalam mendorong Pemilu Inklusif: Studi Kasus Pilkada di DIY 2024 - Darojat, Abdurrahman; Sujiwa, Krisna; Arief, Dikdik Baihaqi (Jurusan Ilmu Politik, FISIP, Universitas Andalas, 2025)
This research aims to identify the strategies of disabled groups to promote inclusive elections in the 2024 regional elections in DIY. Disabled groups tend to receive stigma and are associated with the stereotype of being a second-class society, lacking the same abilities as the majority of the population. Disabled groups, as part of the citizenry, are entitled to equal political rights. This research is a qualitative study with a case study approach. The data collection for this research was conducted through in-depth interviews and literature studies. The research results show that accessibility is still a challenge in realizing inclusive elections. The strategies employed by disabled groups to promote inclusive elections in the 2024 regional elections in DIY include collective actions such as community-based campaigns and socialization, political pressure, and litigation-based advocacy